The Correlation Between Students’ Reading Comprehension and Speaking Skill - Hadeli Hadeli; Melinda Roza; Annisa Mawaddah (Institut Agama Islam Negeri Imam Bonjol Padang, 2026)
Reading and speaking are essential language skills that support students in understanding and communicating information effectively. Information gained through reading can enrich students’ knowledge and provide content to be expressed orally. This study aimed to investigate the correlation between students’ reading comprehension and their speaking skill in producing explanation texts at Senior High School 2 Bukittinggi. A correlational research design was employed to examine the relationship between the two variables. The population consisted of 142 eleventh-grade science students distributed across four classes. The sample comprised 36 students selected through cluster random sampling. Data were collected using two instruments: a reading comprehension test and an oral presentation test designed to assess students’ speaking performance in explanation texts. The collected data were analyzed using the Pearson product moment correlation formula, both manually and with statistical software. The findings revealed that the obtained correlation coefficient was lower than the critical value at the 0.05 level of significance, indicating no significant correlation between students’ reading comprehension and speaking skill. In conclusion, higher reading comprehension does not necessarily correspond to better speaking performance, suggesting that these skills may develop independently and require different instructional approaches